Diagnostic Accuracy of Liquid Biomarkers in Airway Diseases: Toward Point-of-Care Applications - Landry, Vivianne; Coburn, Patrick; Kost, Karen; Liu, Xinyu; Li-Jessen, Nicole Y. K. (Frontiers in Medicine, 2022)
Background: Liquid biomarkers have shown increasing utility in the clinical management of airway diseases. Salivary and blood samples are particularly amenable to point-of-care (POC) testing due to simple specimen collection and processing. However, very few POC tests have successfully progressed to clinical application due to the uncertainty and unpredictability surrounding their diagnostic accuracy. Objective: To review liquid biomarkers of airway diseases with well-established diagnostic accuracies and discuss their prospects for future POC applications. Methodology: A literature review of publications indexed in Medline or Embase was performed to evaluate the diagnostic accuracy of liquid biomarkers for chronic obstructive pulmonary disease (COPD), asthma, or laryngopharyngeal reflux (LPR), and COVID-19. Results: Of 3628 studies, 71 fulfilled the inclusion criteria. Sputum and blood eosinophils were the most frequently investigated biomarkers for the management of asthma and COPD. Salivary pepsin was the only biomarker with a well-documented accuracy for the diagnosis of LPR. Inflammatory blood biomarkers (e.g., CRP, D-dimers, ferritin) were found to be useful to predict the severity, complications, and mortality related to COVID-19 infection. Conclusion: Multiple liquid biomarkers have well-established diagnostic accuracies and are thus amenable to POC testing in clinical settings.